Influence of Youth-Friendly Health Campaigns on Teenage Pregnancy Outcomes among Adolescents in Narok West Sub-County, Kenya - Ndaiya Brenda Nashipai; Misati Joseph; Wambu Charles (International Journal of Recent Trends in Multidisciplinary Research, 2026)
Teenage pregnancy remains a major social, public health and socioeconomic concern among adolescents in Kenya, particularly in rural and pastoralist settings where access to appropriate sexual and reproductive health information and adolescent-responsive services may be constrained by stigma, cultural beliefs and socioeconomic conditions. This article examined the influence of youth-friendly health campaigns on teenage pregnancy outcomes among adolescents in Narok West Sub-County, Kenya. The study adopted a positivist orientation and an explanatory sequential mixed-methods design. Questionnaires were administered to 300 adolescents aged 13–19 years, of which 290 were correctly completed and returned, yielding a 96.7% response rate. Youth-friendly health campaigns were measured using four five-point Likert-scale items, while teenage pregnancy outcomes were measured using four corresponding indicators. Descriptive statistics and simple linear regression were conducted using SPSS. The youth-friendly health campaigns constructed a composite mean of 3.450 (SD = 1.126), indicating generally favorable perceptions. Regression results showed a moderate positive relationship between youth-friendly health campaigns and teenage pregnancy outcomes (R = 0.524; R² = 0.275; Adjusted R² = 0.272). The regression model was statistically significant, F(1,288) = 43.736, p < 0.001, and the standardized coefficient was positive and significant (β = 0.524, t = 6.614, p < 0.001; 95% CI [0.368, 0.680]). The null hypothesis was therefore rejected. The findings demonstrate that youth-friendly health campaigns are an important component of adolescent pregnancy-prevention programming, although their explanatory power indicates that complementary family, school, community and socioeconomic interventions remain necessary.